L’ECOLE IVOIRIENNE FACE AUX CONFLITS INTERCOMMUNAUTAIRES. QUELLES CONSEQUENCES SUR LES RENDEMENTS DES ELEVES DE COTE D’IVOIRE ? CAS DE LA COMMUNE DE YOPOUGON - N’guessan, Anon (European Scientific Journal, ESJ, 2014)
Côte d’Ivoire like many West African countries experienced a severe crisis that led to war. However, in this case, the war resulted from a political crisis which has led to several communal conflicts. These conflicts have weakened the Ivorian society sparing no industry. Thus, school which is the state instrument that ensures social advancement and open young people minds through cultural mixing is not exempt because key actors (policy makers, teachers, students and parents) are involved in the crisis at different levels creating an unhealthy atmosphere around school. Such is the context in which this study is conducted. Its general objective is to analyze the adverse effects of a social context stressed by resentment, hatred, rejection of unity etc within the different social groups in Côte d’Ivoire and their negative impacts on teaching-learning process. The results of this survey with 284 subjects show that cohesion in the class-group is poorly impacted by conflicts. However, inter-group conflicts have raised in some students a feeling of rejection which has a negative impact on their school performance.